2007
DOI: 10.1111/j.1445-2197.2006.03990.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Abdominal Fat Distribution After Gastrectomy: Computed Tomography Assessment

Abstract: Patients who underwent gastrectomy lost TAT, VAT and SAT during the postoperative period up to 6 months and the decrease in VAT was greater and more persistent than the decrease in SAT, particularly in the TG group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…In fat tissue, a reduction of 56.1 ± 36.4 % in subcutaneous plus intramuscular adipose tissue and a reduction of 77.4 ± 39.0 % in visceral adipose tissue were observed in this study (data not shown). Previous CT image analyses reported decreases in subcutaneous adipose tissue and visceral adipose tissue of approximately 20-40 % and 50-60 %, respectively [25,26]. These findings suggest that the mass of visceral adipose tissue decreases more than that of subcutaneous plus intramuscular adipose tissue after TG.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In fat tissue, a reduction of 56.1 ± 36.4 % in subcutaneous plus intramuscular adipose tissue and a reduction of 77.4 ± 39.0 % in visceral adipose tissue were observed in this study (data not shown). Previous CT image analyses reported decreases in subcutaneous adipose tissue and visceral adipose tissue of approximately 20-40 % and 50-60 %, respectively [25,26]. These findings suggest that the mass of visceral adipose tissue decreases more than that of subcutaneous plus intramuscular adipose tissue after TG.…”
Section: Discussionsupporting
confidence: 55%
“…These findings suggest that the mass of visceral adipose tissue decreases more than that of subcutaneous plus intramuscular adipose tissue after TG. It has been speculated that the decrease in visceral adipose tissue is caused predominantly by the withdrawal of hypothetical gastric hormonal factors, which could increase fat mobilization or inhibit fat deposition within the visceral cavity [25]. Twenty-six patients (25.5 %) showed a significant loss of skeletal muscle of more than 10 % at 1 year after TG.…”
Section: Discussionmentioning
confidence: 99%
“…Siervo et al[27] also reported that body composition varies with BMI, age and sex. Although a significant reduction in body fat has been reported after gastrectomy, several studies indicated that the reduction in skeletal muscle mass was smaller than reductions in the volume of body fat[28-31]. These previous findings may, in part, explain the smaller body weight loss in patients with low BMI (< 18.5), in which, the proportion of the skeletal muscle supposed to be larger than those of the other relevant preoperative BMI groups.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al . [17] reported a greater loss of visceral fat tissue after TG than after subtotal gastrectomy at 6 months after surgery. At 12 months after surgery, the losses in BMI, total adipose tissue, subcutaneous, and visceral fat tissues were all greater after TG than after subtotal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%